Modeling and Experimental Characterization of Nanocomposite Materials - Hadavinia, Homayoun (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue gathers research from different branches of science and engineering disciplines working on experiments and modelling of nanocomposites into one volume. The Guest Editor welcomes papers dedicated to experimental, computational, and theoretical aspects dealing with many important state-of-the-art technologies and methodologies regarding the synthesis, fabrication, characterization, properties, design, and applications, and both finite element analysis and molecular dynamic simulations, of nanocomposite materials and structures. Full papers covering novel topics, extending the frontiers of the science and technology of nanoreinforced composites are encouraged. Reviews covering topics of major interest will be also considered.
English
Keywords: ab initio; critical yield strength; carbon nanotube; impact buckling; elasticity; molecular dynamics simulation; magnetism; coarse-grained model; 3D fiber-metal laminates; mechanical property; interface; nanocomposites; interface force fields; YN; graphene/Fe composite; cohesive element; stability; ScN; delamination propagation; interfaces; graphene nanoplatelets; nanoindentation; pressure; molecular dynamics; piezoelectric property; temperature effect; Fe-Al; hardness; equivalent fiber; disorder; Fe3Al; elastic modulus; delamination buckling; CNT agglomeration; CNTs/epoxy nanocomposites; boron nitride honeycomb